2019
DOI: 10.15171/apb.2020.002
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Cellular Mechanisms of Flavonoids Radioprotective Effects

Abstract: Considering the remarkable application of radiotherapy in the treatment and diagnosis of various diseases and even nuclear war, it is important to protect healthy tissues and people at risk from the radiation. Currently, there is no ideal and safe radioprotective agent available and we are seeing a great effort to find these agents from natural sources. Phenolic compounds, as well as flavonoid, are presented widely as the second metabolite in plants and they have been considered for investigation according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…Flavonoids are plant-derived compounds with antioxidant, anti-inflammatory and radio-neuro-protective effects [13]. Flavonoids and their metabolites can cross the blood-brain barrier (BBB) [14], which is made up of capillary endothelial cells and basement membrane, neuroglial membrane and glial podocytes, i.e., projections of astrocytes [15], and reach brain cells to reduce brain damage and alleviate neurodegenerative diseases and cognitive impairment [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are plant-derived compounds with antioxidant, anti-inflammatory and radio-neuro-protective effects [13]. Flavonoids and their metabolites can cross the blood-brain barrier (BBB) [14], which is made up of capillary endothelial cells and basement membrane, neuroglial membrane and glial podocytes, i.e., projections of astrocytes [15], and reach brain cells to reduce brain damage and alleviate neurodegenerative diseases and cognitive impairment [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to metformin and quinolone-based antimalarial drugs, anti-psychotics agents such as selective serotonin reuptake inhibitors, tricyclic antidepressants, lithium chloride, and valproic acid are more commonly prescribed with glioma patients following the standard therapy. These antipsychotic drugs’ ability to cross the BBB further highlights their potential to be prioritized as a repurposed drug-based adjuvant in the clinical setting, as reviewed by us previously [ 269 ]. Additionally, these anti-psychotic drugs are well-studied in brain-related disorders and cancer studies.…”
Section: Repurposing Drugs For Hggmentioning
confidence: 97%
“…Flavonoids are a group of bioactive polyphenolic agents structurally diverse with low toxicity [ 269 , 270 ]. They have been studied for their anti-cancer properties in glioma models [ 271 , 272 , 273 , 274 ].…”
Section: Phytochemicals and Nanoparticles In Hggmentioning
confidence: 99%
“…The outstanding properties of polyphenolic compounds have attracted researchers in the field of pharmaceutical science owing to their potent therapeutic efficacy against different diseases and their capacity to be utilized in the production of cosmetics and dietary supplements [ 37 ]. Several studies demonstrated that polyphenolic phytochemical-rich products have potent anti-inflammatory, anticancer, antidiabetic, and antioxidant activities in addition to other multiple health benefits to human organs [ 9 , 38 , 39 , 40 ]. The chemical nature of these components has a crucial impact on the lipid solubility properties, as poor penetration across lipid-rich biological membranes, such as the skin barrier, has been reported, which leads to poor bioavailability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%